2021
DOI: 10.3389/fnbeh.2020.626769
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Physical Exercise to Brain Resilience

Abstract: Increasing attention has been given to understanding resilience to brain diseases, often described as brain or cognitive reserve. Among the protective factors for the development of resilience, physical activity/exercise has been considered to play an important role. Exercise is known to induce many positive effects on the brain. As such, exercise represents an important tool to influence neurodevelopment and shape the adult brain to react to life's challenges. Among many beneficial effects, exercise intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 203 publications
(239 reference statements)
4
38
0
1
Order By: Relevance
“…Ozkara et al have suggested that this may be because physical activity makes the cardiovascular system more efficient, and it does not need to do so much work to mobilize resources to cope with stressors [48]. Physical activity can also enhance the ability of emotional regulation by strengthening individual brain regions and large-scale neural circuits [49], so as to improve the mental resilience of college students. The more physical activity they engage in, the more resilient they will become [50].…”
Section: Discussionmentioning
confidence: 99%
“…Ozkara et al have suggested that this may be because physical activity makes the cardiovascular system more efficient, and it does not need to do so much work to mobilize resources to cope with stressors [48]. Physical activity can also enhance the ability of emotional regulation by strengthening individual brain regions and large-scale neural circuits [49], so as to improve the mental resilience of college students. The more physical activity they engage in, the more resilient they will become [50].…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is known that PE in humans, especially running, acts as an antidepressant intervention by increasing hippocampal volumes and also reversing the age-dependent volume decline [ 204 , 474 ]. In addition, it is commonly accepted that PE contributes to protection against psychiatric disorders [ 475 ]. As mentioned above, in rodents, PE strongly increases neurogenesis [ 150 ], but this direct link is missing in humans, and therefore, interpretation can be only indirect.…”
Section: Resilience: Is Neurogenesis a Resilience Mechanism?mentioning
confidence: 99%
“…Indeed, several pathways resulting in different adaptations related to improved brain structure and function are suggested. These adaptations to exercise are generally viewed as structural, hemodynamic, and molecular in nature which occur either through separate or convergent signaling pathways that ultimately reduce disease risk [ 60 63 ]. The induction of neurotrophic factors, including BDNF, insulin-like growth factor (IGF), and vascular endothelial growth factor (VEGF), is viewed as a central mechanism associated with the benefits of exercise on brain function [ 64 ].…”
Section: Discussionmentioning
confidence: 99%